Physiological Responses Manifested by Some Conventional Stress Parameters and Biophoton Emission in Winter Wheat as a Consequence of Cereal Leaf Beetle Infestation - Lukács, Helga; Jócsák, Ildikó; Somfalvi-Tóth, Katalin; Keszthelyi, Sándor (Frontiers in Plant Science, 2022)
Oulema melanopus L. (Coleoptera: Chrysomelidae) is one of the most serious pests of winter wheat that causes peeling of the epidermis and tissue loss. The complex mapping of the physiological responses triggered by O. melanopus as a biotic stressor in winter wheat has not been fully explored with the help of non-invasive imaging and analytical assays, yet. The aim of the present work was to study the effect of O. melanopus on the physiological processes of winter wheat, especially on the extent of lipid peroxidation and antioxidant activity derived from tissue destruction, as well as photosynthetic ability. The results of the measurements enabled the identification of the antioxidant and lipid-oxidation–related physiological reactions, and they were reflected in the dynamics of non-invasive biophoton emissions. Our non-invasive approach pointed out that in the case of O. melanopus infestation the damage is manifested in tissue loss and the systemic signaling of the biotic stress may have reached other plant parts as well, which was confirmed by the results of antioxidant capacity measurements. These results indicate that the plant reacts to the biotic stress at a whole organizational level. We identified that the antioxidant and lipid-oxidation–related physiological reactions were reflected in the dynamics of two aspects of biophoton emission: delayed fluorescence and ultra-weak bioluminescence. Our research further supported that the non-invasive approach to stress assessment may complete and detail the traditional stress indicators.